Systematic review with meta‐analysis: the prevalence of coeliac disease in patients with osteoporosis. Issue 6 (8th July 2018) - Laszkowska, M.; Mahadev, S.; Sundström, J.; Lebwohl, B.; Green, P. H. R.; Michaelsson, K.; Ludvigsson, J. F.
Summary: Background: Earlier studies have produced highly varying risk estimates for the prevalence of coeliac disease (CD) in osteoporosis. Aims: To investigate the prevalence of CD among individuals with osteoporosis. Methods: We conducted a systematic review of articles published in PubMed, Medline or EMBASE through May 2017 to identify studies looking at prevalence of CD in patients with osteoporosis. Search terms included "coeliac disease" combined with "fractures", "bone disease", "bone density", "densitometry", "osteoporos*", "osteomal*", "osteodys" or "dexa" or "dxa" or "skelet". Non‐English papers with English‐language abstracts were included. We used fixed‐effects inverse variance‐weighted models, and tested heterogeneity through subgroup analysis as well as through meta‐regression. Results: We identified eight relevant studies, comprising data from 3188 individuals with osteoporosis. Of these, 59 individuals (1.9%) had CD. A weighted pooled analysis demonstrated biopsy‐confirmed CD in 1.6% (95% CI = 1.1%‐2.0%) of individuals with osteoporosis. The heterogeneity was moderate ( I 2  = 40.1%), and influenced by the underlying CD prevalence in the general population. After adding four studies (n = 814) with CD defined as positive tissue transglutaminase or endomysial antibodies, the pooled prevalence was comparable (1.6%; 95% CI = 1.2%‐2.0%). Conclusions: About 1 in 62 individuals with osteoporosis, or 1.6%, have biopsy‐verified CD. This prevalence is comparable to that in the general population. These findings argue against routinely screening patients with osteoporosis for CD, which is contrary to current guideline recommendations. Additional studies are needed to determine the true utility of such screening programs.